Pengaruh Kualitas Layanan Medis, Kelengkapan Medis, dan Tarif Medis Terhadap Kunjungan Ulang Pasien Poli Bedah Digestive Rsud Dr. Iskak Kabupaten Tulungagung - Rahadyan Anugraha Gitta Satriatama (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effects of medical service quality, medical equipment completeness, and medical fees on patient revisit intention at the Digestive Surgery Outpatient Clinic of dr. Iskak Regional General Hospital, Tulungagung Regency. This study employed a quantitative approach with an associative research design. Data were collected through questionnaires distributed to 84 respondents who were patients of the Digestive Surgery Outpatient Clinic of dr. Iskak Regional General Hospital, Tulungagung Regency, using purposive sampling. The respondents were patients who had previously made repeat visits to the Digestive Surgery Outpatient Clinic of dr. Iskak Regional General Hospital, Tulungagung Regency, and were domiciled in the Kediri Residency area. Data analysis was conducted using validity tests, reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination test. The results showed that medical service quality had a positive and significant effect on patient revisit intention, with a coefficient value of 0.864 and a significance level of 0.000. Medical equipment completeness also had a positive and significant effect on patient revisit intention, with a coefficient value of 0.256 and a significance level of 0.000. In addition, medical fees had a negative and significant effect on patient revisit intention, with a coefficient value of -0.271 and a significance level of 0.050. These findings indicate that medical service quality, medical equipment completeness, and medical fees have an impact on patient revisit intention at the Digestive Surgery Outpatient Clinic of dr. Iskak Regional General Hospital, Tulungagung Regency.